Answer:
The answer is 38
Step-by-step explanation:
Answer:
Step-by-step explanation:
y=a(x-0)(x-2)
=a(x^2-2x)
=a(x^2-2x+1-1)
or y=a(x-1)^2-a
(1,5) lies on it.
5=a(1-1)^2-a
5=0-a
or a=-5
so y=-5(x-1)^2+5
Y=Mx+b ddd d d d d d sans
Expanding the given expressions using Foil:
1)(–7x + 4)(–7x + 4) =![7x^{2}-28x-28x+16=49x^{2}-56x+16](https://tex.z-dn.net/?f=7x%5E%7B2%7D-28x-28x%2B16%3D49x%5E%7B2%7D-56x%2B16)
2) (–7x + 4)(4 – 7x)=![-28x+49x^{2}+16-28x=49x^{2}-56x+16.](https://tex.z-dn.net/?f=-28x%2B49x%5E%7B2%7D%2B16-28x%3D49x%5E%7B2%7D-56x%2B16.)
3)(–7x + 4)(–7x – 4)=
=![49x^{2}-16.](https://tex.z-dn.net/?f=49x%5E%7B2%7D-16.)
4)(–7x + 4)(7x – 4)=![49x^{2}+28x+28x-16=49x^{2}+56x-16.](https://tex.z-dn.net/?f=49x%5E%7B2%7D%2B28x%2B28x-16%3D49x%5E%7B2%7D%2B56x-16.)
The third option that is (–7x + 4)(–7x – 4) is difference of two squares.